COMPARE RESULTS OF HEMOSTASIS DISORDERS IN PATIENTS WITH METABOLIC SYNDROME - Allamurodova Feruza Yakubovna (Galaxy International Interdisciplinary Research Journal, 2022)
Metabolic syndrome is a complex symptom complex, manifested together with arterial hypertension, abdominal-visceral obesity, dyslipidemia, impaired glucose tolerance, insulin resistance, hyperinsulinemia, hyperuricemia, microalbuminuria, hemostasis disorders. In the study, laboratory analyzes of urban and rural residents and their deviations from the norm were analyzed, and the importance of the place of residence of the population in the development and complications of metabolic syndrome was studied.